Monitoring and Mitigation Works in Unsaturated Archaeological Deposits*. (2nd July 2016) - Matthiesen, Henning; Hollesen, Jørgen; Dunlop, Rory; Seither, Anna; de Beer, Johannes
Abstract : Monitoring of the archaeological deposits at the World Heritage Site Bryggen in Bergen has been ongoing since 2001. In latter years a large-scale project of mitigation works has been carried out, resulting in the creation of a water-management system aimed at raising groundwater-levels and increasing soil moisture content in areas with poor preservation conditions. Oxygen is a key parameter in the decay of archaeological material in the unsaturated zone, and the monitoring at Bryggen includes in situ monitoring of oxygen concentrations and comparison to soil moisture content, temperature, groundwater-level, precipitation and soil reactivity. This is used to document where and when decay takes place and to estimate "how wet is wet enough" in order to reduce the oxygen diffusion and the decay rate to an acceptable level. The results show that even small changes in the soil moisture can have a large impact on the oxygen dynamics in the ground.